2007
DOI: 10.1063/1.2732821
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interfacial layer control using Gd2O3 in HfO2 gate dielectric on GaAs

Abstract: Structural and electrical properties of HfO 2 and HfO 2 /Gd 2 O 3 gate stacks on p-GaAs substrates have been investigated. It has been demonstrated that the presence of thin layer of Gd 2 O 3 between HfO 2 and GaAs improves metal-oxide-semiconductor device characteristics such as interface state density, accumulation capacitance, frequency dispersion, and leakage current. It is also found that HfO 2 /Gd 2 O 3 stack can reduce the interfacial GaAs-oxide formation, thus reduce the outdiffusion of elemental Ga an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 21 publications
(23 reference statements)
4
42
0
Order By: Relevance
“…For example, Shahrjerdi et al 5 reported hysteresis values of 380 and 430 mV, respectively, with as-deposited Al 2 O 3 on hydroxylated and sulfur-passivated GaAs. The hysteresis voltages with HfO 2 and HfO 2 / Gd 2 O 3 on p-GaAs were found to be 300 and 200 mV, respectively, as reported by Dalapati et al 13 However, the lowest value of hysteresis with Al 2 O 3 was mentioned to be 100 mV by Yang et al 14 So, the efficacy of sulfur passivation on p-GaAs with ZrO 2 as a high-k dielectric for GaAs MOS devices with a hysteresis of 150 mV, as observed in the present study, is noteworthy.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…For example, Shahrjerdi et al 5 reported hysteresis values of 380 and 430 mV, respectively, with as-deposited Al 2 O 3 on hydroxylated and sulfur-passivated GaAs. The hysteresis voltages with HfO 2 and HfO 2 / Gd 2 O 3 on p-GaAs were found to be 300 and 200 mV, respectively, as reported by Dalapati et al 13 However, the lowest value of hysteresis with Al 2 O 3 was mentioned to be 100 mV by Yang et al 14 So, the efficacy of sulfur passivation on p-GaAs with ZrO 2 as a high-k dielectric for GaAs MOS devices with a hysteresis of 150 mV, as observed in the present study, is noteworthy.…”
Section: Resultssupporting
confidence: 80%
“…Ultrathin sulfur layer on GaAs reduces the formation of GaAs native oxides and also prohibits outdiffusion of elemental Ga and As in the oxide layers. 3,13 The flatband voltage for the passivated GaAs MOS device was found to be Ϫ1.10 V, whereas for the nonpassivated GaAs device, it was Ϫ1.43 V. The hysteresis found in Fig. 4 could be attributed to the charge trapping into the oxide.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Driven by the high intrinsic electron mobility, III-V channel MOSFETs have been illustrated by using different high-k dielectrics such as HfO 2 [421], Al 2 O 3 [77,422], Gd 2 O 3 [423], and Ga 2 O 3 (Gd 2 O 3 ) [424]. Different methods have been employed to passivate the III-V substrate.…”
Section: Iii-v High Mobility Semiconductor For N-mos Applicationsmentioning
confidence: 99%
“…C Germanium has become more and more attracting as next generation metal-oxide-semiconductor field-effect transistors (MOSFET) channel material for future CMOS devices owing to several of its attractive properties including higher electron and hole mobility for larger drive current and smaller mobility band-gap for supply voltage scaling as compared to the conventional channel material Si. 1,2 However, the absence of high quality MOS interface compared to that of SiO 2 /Si interface retards the development of Ge MOSFETs devices with high performance due to the volatility of the GeO x species. 3 Therefore, for the successful realization of Ge-based MOSFETs, there are still a number of fundamental issues to be solved.…”
mentioning
confidence: 99%